MUTU FISIK DAN MIKROSTRUKTUR KAMABOKO IKAN KURISI (Nemipterus nematophorus) DENGAN PENAMBAHAN KARAGINAN - Titiek Indhira Agustin (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Carrageenan is a natural material extracted from red algae especially Eucheuma sp, kappa-carrageenan extracted from E. cottonii and iota-carrageenan from E. spinosum. Kappa and iota carrageenans have very similar structures and  have functional properties as gelling agent. The purpose of this research  is to find out the effect of carrageenan on the physical and microstructure quality of kamaboko. This research used a  complete randomized design by doing four treatments, namely K(-): without carrageenan, K(+): by adding commercial carrageenan, K(k): by adding  kappa-carrageenan and K(i): by adding  iota-carrageenan. The result showed that the additional carrageenan had significant effects on the physical and microstructure quality of the kamaboko. The best treatment of kamaboko was by adding of commercial carrageenan (K(+)). The characteristics of kamaboko were folding test (5), springness (7.3), gel strength 2872.62g/cm  and whiteness (W*) 73.78. The microstructure of kamaboko with adding of commercial carrageenan and kappa-carragenan exhibited a porous structure while the microstructure of kamaboko added  with iotacarrageenan exhibited a compact and smooth structure.Keywords: carrageenan, microstructure, kamaboko, Nemipterus nematophorus